Gene Expression in Response to Exercise in Patients with Chronic Fatigue Syndrome: A Pilot Study - Keech, Andrew; Vollmer-Conna, Ute; Barry, Benjamin K.; Lloyd, Andrew R. (Frontiers in Physiology, 2016)
Chronic fatigue syndrome (CFS) is a debilitating disorder of unknown pathogenesis, characterised by fatigue, which is exacerbated after minimal exercise. We examined the effect of a single bout of aerobic exercise on leucocyte mRNA expression of genes putatively linked to exaggerated afferent signalling as an under-pinning of the fatigue state. A carefully-characterised sample of patients with CFS (N = 10) and healthy matched control participants (N = 12) were included. Participant ratings of fatigue and other symptoms, as well as blood samples, were obtained at baseline, and five other time-points up to 72 hours after 25 minutes of moderate-intensity cycling exercise. Leucocyte mRNA of 19 metabolite-sensing, adrenergic, immune and neurotransmission genes was examined using quantitative polymerase chain reaction. Patients with CFS reported substantial fatigue, functional impairment and poor sleep at baseline (all p < 0.02), and exercise immediately induced worsened patients’ fatigue (effect size, ES = 1.17). There were no significant changes in gene expression after exercise and patients did not differ from control participants at any time point. Higher levels of expression of ficolin (FCN1) and a purinergic receptor (P2RX4) in patients with CFS were found when all time points were combined. Patients with CFS did not show significant exercise-induced changes in leucocyte mRNA of 19 metabolite-sensing, adrenergic, immune and neurotransmission genes despite a prominent exacerbation of fatigue.